The Relationship between Internet Addiction and Depression in Adolescents - Ahmad, Tazlim (Journal of Asian-african Focus in Health, 2023)
Internet addiction is defined as an excessive use of the internet that can interfere individual's health and cause psychological, social and school problems. One of the psychological impact of internet addiction is the decreased of quality time with friends and family that can cause social isolation. This condition can lead to depression. Internet addiction is characterized by excessive or poorly controlled preoccupations, urges or behaviours regarding computer use and internet access that lead to impairment or distress. The condition has attracted increasing attention in the popular media and among researchers, and this attention has paralleled the growth in computer (and Internet) access.